Public environmental concern in China: Determinants and variations. (March 2016) - Liu, Xinsheng; Mu, Ren
Highlights: We use national survey data and provincial statistics to examine the variations and determinants of public environmental concern in China. The environmental concern is not among the top-ranked issue concerns in China overall. Only in the urban areas and in the east-coastal region, does environmental protection feature as a rather important issue. Location contextual factors such as economic development and environmental risk explain most of the variations in public environment concern. Sociodemographics exert little effect on environmental concern in less developed areas, but the effect becomes prominent in more developed areas. Abstract: How much are Chinese people and various citizen groups concerned about the environment relative to other major public problems? What are the key factors and to what extent do these factors shape individual Chinese environmental concern? Based on a micro-macro model and a county fixed model proposed in this study, we employ nationwide representative public opinion survey data and provincial statistics to examine the determinants and variations of public environmental concern in China. The data shows that environmental concern is not among the top-ranked issue concerns in China overall, but in the urban areas and in the east-coastal region environmental protection features as a rather important issue. Our regression analyses further demonstrate that the Chinese environmental concern is significantly affected by both micro-level socio-demographic variables and macro-level regional economic conditions and environmental risks. In the east-coastal region, such individuals as urbanites with high income are most environmentally concerned. There is a lack of concern over environmental issues among the public in the west region, where little association between individual sociodemographics and their environmental concern is detected. In the central-northeast region, education effect is evident in the rural area. Location contextual factors such as economic development and environmental risk account for most of the observed variations in public environment concern.